RNA antagonists - a new class of antisense drugs. - Orum, H. (IEEE Engineering in medicine and biology magazine)
The locked nucleic acid (LNA) chemistry brings truly stunning affinity and high biostability to the world of nucleic acids. In turn, these features enable the design of shorter-than-usual oligos that exhibit unprecedented potency, good specificity, high biostability, good biodistribution, and low toxicity. Such LNA-oligos have been termed RNA antagonists to signal the strong belief that they will transform antisense therapy into a robust drug platform. It is further expected that this new class of drugs will be compatible with less frequent and more convenient dosing regimens than those currently employed with first generation DNAPS-oligos (DNA-oligos based on phosphorothioate chemistry). For instance, their enhanced biostability may well enable weekly, or even biweekly, dosing. Likewise, the apparent absence of acute toxicities associated with therapeutically sized DNAPS-oligos may well enable RNA antagonists to be administered by direct bolus injection by healthcare professionals or even by the patients themselves.